Pseudomonas aeruginosa and acute rejection independently increase the risk of donor‐specific antibodies after lung transplantation. Issue 4 (24th December 2019) - Kulkarni, Hrishikesh S.; Tsui, Kevin; Sunder, Suraj; Ganninger, Alex; Tague, Laneshia K.; Witt, Chad A.; Byers, Derek E.; Trulock, Elbert P.; Nava, Ruben; Puri, Varun; Kreisel, Daniel; Mohanakumar, Thalachallour; et al.
Abstract : Factors contributing to donor‐specific HLA antibody (DSA) development after lung transplantation have not been systematically evaluated. We hypothesized that the isolation of Pseudomonas aeruginosa in respiratory specimens would increase the risk of DSA development. Our objective was to determine the risk of DSA development associated with the isolation of Pseudomonas aeruginosa after lung transplantation. We conducted a single‐center retrospective cohort study of primary lung transplant recipients and examined risk factors for DSA development using Cox regression models. Of 460 recipients, 205 (45%) developed DSA; the majority developed Class II DSA (n = 175, 85%), and 145 of 205 (71%) developed DSA to HLA‐DQ alleles. Univariate time‐dependent analyses revealed that isolation of Pseudomonas from respiratory specimens, acute cellular rejection, and lymphocytic bronchiolitis are associated with an increased risk of DSA development. In multivariable analyses, Pseudomonas isolation, acute cellular rejection, and lymphocytic bronchiolitis remained independent risk factors for DSA development. Additionally, there was a direct association between the number of positive Pseudomonas cultures and the risk of DSA development. Our findings suggest that pro‐inflammatory events including acute cellular rejection, lymphocytic bronchiolitis, and Pseudomonas isolation after transplantation are associated with an increased risk of DSA development. Abstract : The authors show that proinflammatory events after lung transplantation, such as acute cellular rejection, lymphocytic bronchiolitis, and Pseudomonas isolation, are associated with an increased risk of developing donor‐specific antibodies. See the editorial by Weigt and Snyder on page 920 .